Assembly processes and co-occurrence relationships in the bacterioplankton communities of a large river system - He Sun (Elsevier, 2021)
The incoming water area of the Central Line Project of the South-to-North Water Diversion comprises the upper reaches of the Han River in China. Bacterioplankton are important members of river ecosystems. However, the mechanisms (deterministic or stochastic processes) regulating planktonic bacterial community structure in the upper Han River are not well understood. Herein, we documented the spatiotemporal patterns, assembly processes, and co-occurrence relationships of the planktonic bacterial communities in the Han River and its tributaries. Seasonal variations in bacterioplankton communities were clearly observed and were more obvious than spatial differences. The planktonic bacterial community showed a significant distance (dendritic distance) decay pattern during the two sampling periods, and the distance decay pattern was stronger in spring than in the other season. Network analysis showed that bacterial community networks displayed non-random co-occurrence patterns, and significant differences in the topological properties of empirical and random networks (average clustering coefficient, average path length, and average degree) were found. Compared to those of the tributaries, the network of the mainstem had the lowest modularity; this may be caused by the significant difference in biodiversity between the mainstem and the tributaries. Redundancy analysis revealed that pH exhibited significant effects on the planktonic bacterial community in both seasons. However, variation partitioning analysis showed that spatial factors (stochastic processes) contributed more to explaining community assembly than environmental factors during the two seasons. In addition, the neutral community model can also explain a large part of the community variation observed during the autumn and spring (R2 = 0.817 and 0.808, respectively). This study shows that seasonal variation in the bacterial community is greatly influenced by seasonal environmental variation. However, stochastic processes dominantly affect the structure of the bacterioplankton community within seasons. In order to effectively manage and protect microbial diversity, managers consider not only local species diversity, but also the effect of regional species dispersal.